MODERN APPROACHES TO PREVENTION AND REHABILITATION OF ADHESIVE DISEASES IN PATIENTS WITH EXTERNAL GENITAL ENDOMETRIOSIS - Farrukh O. Abidov; Gulnara D. Matrizaeva; Zulkhumor F. Djumaniyazova (Central Asian Journal of Medicine, 2024)
It is known that these methods can reduce the degree of the inflammatory process and the frequency of adhesion formation, but there is no confirming clinical and experimental statistical data on this issue. That is why it is especially important to search for not only new mechanisms leading to the formation of adhesions in the pelvic organs, but also to develop methods for the prevention and treatment of adhesions, which will improve the tactics of managing such patients. Anamnesis, general clinical and gynecological examination were collected.